A Rational Reconfiguration of Electrolyte for High‐Energy and Long‐Life Lithium–Chalcogen Batteries. Issue 23 (4th May 2020) - Wang, Wen‐Peng; Zhang, Juan; Yin, Ya‐Xia; Duan, Hui; Chou, Jia; Li, Sheng‐Yi; Yan, Min; Xin, Sen; Guo, Yu‐Guo
Abstract: Lithium–chalcogen batteries are an appealing choice for high‐energy‐storage technology. However, the traditional battery that employs liquid electrolytes suffers irreversible loss and shuttle of the soluble intermediates. New batteries that adopt Li + ‐conductive polymer electrolytes to mitigate the shuttle problem are hindered by incomplete discharge of sulfur/selenium. To address the trade‐off between energy and cycle life, a new electrolyte is proposed that reconciles the merits of liquid and polymer electrolytes while resolving each of their inferiorities. An in situ interfacial polymerization strategy is developed to create a liquid/polymer hybrid electrolyte between a LiPF6 ‐coated separator and the cathode. A polymer‐gel electrolyte in situ formed on the separator shows high Li + transfer number to serve as a chemical barrier against the shuttle effect. Between the gel electrolyte and the cathode surface is a thin gradient solidification layer that enables transformation from gel to liquid so that the liquid electrolyte is maintained inside the cathode for rapid Li + transport and high utilization of active materials. By addressing the dilemma between the shuttle chemistry and incomplete discharge of S/Se, the new electrolyte configuration demonstrates its feasibility to trigger higher capacity retention of the cathodes. As a result, Li–S and Li–Se cells with high energy and long cycle lives are realized, showing promise for practical use. Abstract : The rational reconfiguration of an electrolyte enabled by an in situ interfacial polymerization strategy is demonstrated. This strategy endows Li–S and Li–Se batteries with high capacity, stable cycling, and excellent rate performances simultaneously, and may become a new pathway toward the large‐scale and cost‐effective applications of future Li metal batteries.